The effects of alternative policies on students in ITM: a case study in modelling complex systems using signed digraphs / Nasaruddin Zenon and Rosmah Ali - Zenon, Nasaruddin; Ali, Rosmah (Universiti Teknologi MARA Cawangan Pahang, 1989)
Most problems involving society are very complex as they involve many interrelating factors. Quite a number of these factors are hard to identify or quantify because of their subjective nature. Thus in many mathematical models of complex systems there will normally be some degree of imprecision. One way to reduce imprecision is by using signed digraphs to build simple mathematical models of complex problems based upon minimal information. In this paper we shall use signed digraphs to study the effects of alternative policies on students in ITM. At the same time we will investigate the mathematical interpretation of behavioral science theory pertaining to the sustainance and channelling of motivation by society and organization. We will see that there is a very strong connection between the Expectancy Theory by Lyman Porter and Edward E. Lawler III and the observations made by Maruyama (1963). It should be noted here that the overall signed digraph for the effects of alternative policies on students in ITM is extremely complex as shown in Figure 5. However, by carefully studying the underlying structural characteristics of the signed digraph and using the theory of graphs we can partition the signed digraph into components. We will study the digraphs component wise and derive the conclusions from there.